Análisis del aumento de seguidores y de la presencia multiplataforma de la clase política en Facebook, Twitter e Instagram en campañas electorales (2011-2019) - Dr. José GAMIR-RÍOS,Dra. Lorena CANO-ORÓN,Dr. Tomás BAVIERA (Fonseca, Journal of Communication, 2023)
The participation of politicians in social media is increasingly necessary in order to gain visibility. However, the logic of content dissemination is very different from conventional media. In social media, building a broad and varied base of followers facilitates a greater impact of the message. This article analyses the influence of various individual factors of the candidates on two aspects of the process: variation in the number of followers and multiplatform presence.